El síndrome anorexia caquexia - Rivera, Fernando; López-vega, José Manuel; López, Carlos; López, Ana; Vega, Mª Eugenia; Sanz, Jaime (Psicooncología, 2004)
The anorexia-cachexia syndrome is a paraneoplasic, metabolic disorder characterized by the appearance of appetite decrease, loss of weight and muscular mass atrophy, which in spite of a correct caloric and nutritional contribution is not achieved to solve. This entity is frequent among patients with malignant tumors. And its result, the malnutrition, drives to a series of complications in the shape of alterations at immune system and related to the oncological treatments, attributing to these patients a worse prognosis. The fisiopathology is explained by the existence of a deregulation at hypothalamic center that has the control of the appetite consequence of the production of several cytokines. According to the irreversibility of the syndrome, once it is established, the most relevant aspect to manage it will be the preventive measurements and obviously a good psycho-emotional support from the sanitary professionals.